Composite materials
Patent Information
- Application Number
- JP2026522639
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-11-28
- Filing Date
- 2025-03-28
- Publication Date
- 2026-10-30
AI Technical Summary
【0172】 本明細書は、異常状態にあるか、異常状態の可能性がある製品ないし素子に適用され、前記異常状態に効果的に対応することができる複合材及び消火装置を開示する。例えば、前記複合材等は、前記製品ないし素子を複数含む物品に適用され、いずれか一つの素子ないし製品で発生する正常でない発熱、爆発及び発火に対応し、そのような発熱、爆発及び発火に隣接する他の素子ないし製品への伝播を防止または最小化することができる。前記複合材等はまた、優れた取扱性と保管安定性を示す。本明細書はまた、前記複合材等の用途を提供することができる。
Smart Images

Figure 2026536529000001_ABST
Abstract
Description
[Technical Field]
[0001] This application claims priority rights based on Korean Patent Application No. 10-2024-0043098 dated March 29, 2024, and Korean Patent Application No. 10-2024-0174269 dated November 28, 2024, and all content disclosed in the documents of said Korean Patent Applications is included as part of this Specification.
[0002] This specification discloses composite materials, fire extinguishing systems including the composite materials, and applications of the composite materials and fire extinguishing systems. [Background technology]
[0003] While the importance of technologies for handling heat generated from products is increasing, processing, managing, and controlling heat in products composed of multiple heat-generating elements remains a challenging problem.
[0004] For example, preventing so-called TR (Thermal Runaway) or TP (Thermal Propagation) phenomena that occur in battery modules or battery packs is extremely important. A battery module or battery pack contains multiple battery cells or multiple battery modules, which are located relatively adjacent to each other.
[0005] In such a structure, the phenomenon in which abnormal heat generation, ignition, and / or explosion occurring in one battery cell and / or battery module propagates in a chain reaction to other adjacent battery cells, etc., is called the TR or TP phenomenon. Such chain ignitions and chain explosions caused by the TR or TP phenomenon must be controlled from a stability standpoint. [Overview of the project] [Problems that the invention aims to solve]
[0006] This specification discloses composite materials, fire extinguishing systems, and their applications. This specification aims to disclose composite materials and fire extinguishing systems that are applicable to products or elements in which abnormal conditions occur or are likely to occur, and that can effectively respond to such abnormal conditions.
[0007] For example, the composite materials and fire extinguishing devices disclosed herein are applied to articles containing multiple such products or elements, and can prevent or minimize the propagation of an abnormal condition occurring in one product or element to other products or elements.
[0008] This specification also aims to disclose composite materials and fire extinguishing systems having excellent handling and storage stability. This specification also aims to disclose applications of composite materials and fire extinguishing systems. [Means for solving the problem]
[0009] Of the physical properties mentioned herein, those affected by temperature are those measured at room temperature unless otherwise specified.
[0010] The term "room temperature" refers to a natural temperature that has not been artificially heated or cooled, and means any temperature within the range of approximately 10°C to 30°C, for example, a temperature of approximately 23°C or 25°C.
[0011] Unless otherwise specified, the unit of temperature referred to herein is °C.
[0012] In this specification, if pressure affects the results of any physical property, unless otherwise specified, the physical property is the one measured at normal pressure.
[0013] The term "normal pressure" refers to the natural pressure that has not been artificially pressurized or depressurized, and typically refers to a pressure in the range of approximately 700 mmHg to 800 mmHg.
[0014] Among the physical properties referred to in the present specification, in cases where humidity affects the results, unless otherwise specified, the physical properties are those measured at the normal temperature and normal pressure conditions under humidity that is not artificially adjusted.
[0015] In the present specification, the term abnormal state refers to a state where abnormal heat generation, ignition and / or explosion occurs in a certain product or element, or there is a risk of the aforementioned abnormal heat generation, ignition and / or explosion.
[0016] In the present specification, the term normal state refers to a state of a certain product or element that is not the aforementioned abnormal state.
[0017] The present specification discloses a composite material.
[0018] The present specification further discloses a fire extinguishing apparatus comprising the aforementioned composite material.
[0019] The fire extinguishing apparatus includes a case having a sealed space inside, and the composite material present in the aforementioned internal sealed space.
[0020] For example, the fire extinguishing apparatus may include a case, and the composite material may be present inside the case. The case has a sealed space inside, and the composite material may be present in such a sealed space.
[0021] The case is a container that holds the aforementioned composite material. The case has a sealed space inside. That the case has a sealed space inside means a state where the sealed space is formed inside the case, or a state where a certain space exists inside the case and the space is not in a sealed state, but the case is configured such that a sealed space can be formed by sealing the open portion. The aforementioned sealed space means a space formed such that components such as the composite material do not substantially flow out to the outside under normal conditions.
[0022] In one example, the case may include a portion having a predetermined range of WVTR (Water Vapor Transmission Rate) as described later. For example, at least the sealed space in which the composite material exists may be substantially surrounded by a portion having a predetermined range of WVTR (Water Vapor Transmission Rate) as described later.
[0023] The case has a vent region. The term "vent region" can mean a region that is sealed in a first state and exists to maintain that sealed state, but is opened in a second state so that all or part of the substance inside the space can be discharged. The second state can mean, for example, an abnormal state as described later, and the first state can mean a normal state as described later. Such a vent region can be formed in the manner described later.
[0024] In one example, the case may include portions having a predetermined range of WVTR (Water Vapor Transmission Rate). For example, a sealed space inside the case may, in a sealed state, be surrounded by a material having a WVTR within the range described below. In the above, the fact that a sealed space is surrounded by a material having a specific WVTR in a sealed state means that the space is substantially surrounded by the material, for example, that 80% to 100%, 85% to 100%, 90% to 100%, 95% to 100%, or substantially 100% of the area of the case forming the sealed space has the specific WVTR. The upper limit of such WVTR (Water Vapor Transmission Rate) may be around 10, 9.5, 9, 8.5, 8, 7.5, 7, 6.5, 6, 5.5, 5, 4.5, 4, 3.5, 3, 2.5, 2, 1.5, 1, 0.5, 0.45, 0.4, 0.35, 0.3, 0.25, 0.2, 0.15, 0.1, 0.05, 0.01, 0.005, or 0.001, and its lower limit may be around 0, 0.1, 0.2, 0.3, 0.4, or 0.5. The WVTR may be within a range where it is less than or equal to any one upper limit arbitrarily selected from the listed upper limits; or it may be greater than or equal to or greater than any one lower limit arbitrarily selected from the listed lower limits, while being less than or equal to any one upper limit arbitrarily selected from the listed upper limits. Having such a WVTR ensures storage stability for the composite material present inside the sealed space, and allows the fire extinguishing system to perform its intended fire extinguishing action more efficiently.
[0025] The unit of the aforementioned WVTR (Water Vapor Transmission Rate) is g / m³. 2 It is a day and can be evaluated using the method described in "6. WVTR (Water Vapor Transmission Rate) Evaluation" of the Examples section of this specification.
[0026] The fire extinguishing device is configured to maintain a composite material in a sealed space under normal conditions, and to effectively release the vaporized substance inside to the outside under abnormal conditions.
[0027] This effect will be explained assuming that the fire extinguishing device is applied to a battery module.
[0028] Figure 1 is a schematic diagram showing the case where the fire extinguishing device (S) is applied to a battery module. As shown in Figure 1, the battery module can be configured by arranging a plurality of battery cells (11, 12, 13, 14, 15, 16) adjacent to each other, and the fire extinguishing device (S) can be placed between the battery cells (for example, between 12 and 13 and / or between 14 and 15 in Figure 1).
[0029] The fire extinguishing device (S) maintains vaporized material inside under normal conditions. In abnormal conditions, the internal material is ejected from the fire extinguishing device (S) through the vent area (dotted arrow in Figure 1), and the ejected internal material can respond to the heat generation, flames, and / or explosions in the abnormal conditions. Figure 1 shows a case where the internal material is ejected from both the upper and lower ends of the fire extinguishing device (S), but the ejection direction is not limited to Figure 1. The ejection direction may be one direction of the fire extinguishing device (S), or it may be two or more directions.
[0030] For a fire extinguishing system to effectively perform its functions in an abnormal state, it is required that vaporized substances and the like that present inside the case in a normal state be stably maintained, that the internal substances be able to be quickly discharged to the outside when an abnormal state occurs, and that the vaporized substances present inside the case in an abnormal state be able to be discharged to the outside in a state where they have been vaporized as much as possible.
[0031] For the fire extinguishing system to perform its function effectively even in an abnormal state, the vaporization rate of the vaporizable substance must be appropriately maintained. When the vaporizable substance vaporizes at an appropriate rate, it is possible to prevent the collapse of the internal pores due to changes in surface tension, etc., after the consumption of latent heat.
[0032] The fire extinguishing devices disclosed herein can satisfy the above requirements.
[0033] The principle by which the fire extinguishing device performs the above-mentioned function will be explained.
[0034] Figure 2 is a diagram showing only the fire extinguishing device (S) in Figure 1. In a configuration similar to that in Figure 1, if abnormal heat generation, abnormal ignition, and / or abnormal explosion occurs in at least one of the battery cells adjacent to the fire extinguishing device (S), a certain level of heat or higher will be instantaneously applied to the fire extinguishing device, as indicated by the solid arrows in Figure 2. In Figure 2, in the sealed internal space of the fire extinguishing device case (1001), vaporized material propagates randomly in all directions within the space, as indicated by the dotted arrows. At this time, if the WVTR of the portion forming the sealed space of the case (1001) is within the aforementioned range, the vaporized gas cannot be released to the outside, and the inside of the case (1001) becomes extremely high-pressure. At this time, if the vent region (1002) of the case is configured to be opened instantaneously at a certain level of high pressure, the vent region (1002) is opened instantaneously in the high-pressure state, and the gas inside is rapidly discharged to the outside through the opened vent region (1002).
[0035] If the WVTR of the case is high, the pressure inside the case (1001) does not increase effectively in an abnormal state. As a result, the vent area (1002) may not open effectively, or even if the vent area (1002) is opened, the internal pressure may be insufficient, preventing all of the internal gas from being discharged to the outside, or the discharge rate may not be adequately ensured.
[0036] By keeping the case's WVTR low, the storage stability of the internal materials can also be effectively ensured under normal conditions.
[0037] The method for forming the vent region (1002) is not particularly limited. The vent region can be formed by designing a certain area of the case forming the sealed space so that it can be opened when a certain level of pressure and / or heat is applied. For example, if a part of the case forming the sealed space is configured to have lower strength than other areas, the increased internal pressure can open the part with lower strength. Alternatively, a method can be used in which the sealed space is formed by sealing using a hot melt material, so that opening occurs due to melting at a predetermined temperature. Another method is to make only a certain part of the case forming the sealed space thinner than other areas, thereby forming the vent region. Such methods for forming a vent region can be easily adopted by those skilled in the art.
[0038] For example, when the fire extinguishing device is applied to a battery module or pack, for convenience of application, the case may be a rectangular case, a pouch-type case, and / or a cylindrical case, such as a battery cell. In such cases, a vent area can also be formed by controlling the bonding strength of the lid that forms a sealed space in the rectangular or cylindrical case.
[0039] The aforementioned case can be constructed using known materials, provided that they can satisfy the aforementioned WVTR requirements, and the materials may have a single layer or a laminated structure of two or more layers.
[0040] For example, the case can be formed using a suitable organic and / or inorganic layer made of a material capable of exhibiting the aforementioned WVTR range.
[0041] As the organic layer, for example, a known polymer film or sheet can be used. Examples of organic films include cellulose polymer films; COP (cycloolefin copolymer) films; acrylic polymer films; polyolefin films; PVA (polyvinyl alcohol) films; PVC (poly(vinyl chloride)) films, PES (poly ether sulfone) films; PEEK (polyetheretherketon) films; PPS (polyphenylsulfone) films; PEI (polyetherimide) films; PEN (polyethylenemaphthatlate) films; polyester films such as PET (poly(ethylene terephthalate)) films; PI (polyimide) films; PSF (polysulfone) films and / or PAR (polyarylate) films.
[0042] For example, the inorganic layer can be a metal layer, a metal oxide layer, a metal nitride layer, or a metal oxynitride layer. For example, the inorganic layer may be a metal layer, a metal oxide layer, a metal nitride layer, or a metal oxynitride layer containing one or more elements selected from the group consisting of In, Sn, Pb, Au, Cu, Ag, Zr, Hf, Zn, Al, Si, La, Ti, and Ni. For example, a foil, sheet, or film of the material can be applied, or a layer formed by vapor deposition or the like on a suitable substrate using the metal layer, metal oxide layer, metal nitride layer, or metal oxynitride layer can be used.
[0043] The material forming the case may be a single layer selected from the inorganic layer and the organic layer, or a multilayer structure in which two or more of the aforementioned layers are laminated.
[0044] The thickness of the inorganic layer and / or organic layer is selected considering the desired physical properties such as WVTR, and is not particularly limited. For example, the lower limit of the thickness may be around 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, or 30 μm, and the upper limit may be around 5,000 μm, 4,000 μm, 3,000 μm, 2,000 μm, 1,000 μm, 500 μm, 200 μm, 150 μm, 100 μm, 90 μm, 80 μm, 70 μm, 60 μm, 50 μm, 40 μm, or 30 μm. The thickness may be within a range where it is less than or equal to any one upper limit arbitrarily selected from the listed upper limits; or within a range where it is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits; or within a range where it is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits, and less than or equal to any one upper limit arbitrarily selected from the listed upper limits.
[0045] The fire extinguishing device may include additional configurations to ensure that the above action is performed more effectively.
[0046] For example, the fire extinguishing device may further include a heat conductive layer. Such a heat conductive layer may be located in an appropriate position within the fire extinguishing device, for example, in the fire extinguishing device, the heat conductive layer may be located between the case and the composite material described later.
[0047] Figure 3 is an example of the fire extinguishing device in Figure 2 in which the heat conductive layer (2001) is added. The heat conductive layer can be located between the case (1001) and the composite material, as shown in Figure 3, but its position is not limited thereto. The heat conductive layer may be located in other positions, such as inside the case, and there may be one or more layers.
[0048] The term "thermal conduction layer" refers to a layer whose thermal conductivity (based on 20°C) is within the range described below. The lower limit of the thermal conductivity (based on 20°C) of the thermal conduction layer may be approximately 15, 18, 20, 50, 100, 150, 200, 250, 300, 350, or 400, and the upper limit may be approximately 2,000, 1,500, 1,000, 900, 800, 700, 600, 500, 400, 300, 200, 100, or 50. The thermal conductivity may be within a range that is greater than or greater than any one lower limit arbitrarily selected from the listed lower limits; or within a range that is greater than or greater than any one lower limit arbitrarily selected from the listed lower limits, while being less than or equal to any one upper limit arbitrarily selected from the listed upper limits. The unit of the thermal conductivity is W / mK.
[0049] The type of thermal conductive layer is not particularly limited as long as it has the aforementioned thermal conductivity. Generally, metal materials can be used as thermal conductive layers because they have excellent thermal conductivity. For example, a layer made of a metal material such as aluminum, gold, pure silver, tungsten, copper, nickel, or platinum can be applied.
[0050] There are no particular restrictions on the thickness of the heat conductive layer, and an appropriate thickness can be set considering the specifications of the fire extinguishing system, etc. For example, the lower limit of the thickness of the heat conductive layer may be around 1 μm, 5 μm, 10 μm, 15 μm, 50 μm, 75 μm, or 90 μm, and the upper limit may be around 500 μm, 400 μm, 300 μm, 200 μm, 100 μm, 50 μm, 40 μm, or 30 μm. The thickness may be within a range that is less than or equal to any one upper limit arbitrarily selected from the listed upper limits; or within a range that is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits; or within a range that is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits, and less than or equal to any one upper limit arbitrarily selected from the listed upper limits.
[0051] As shown in Figure 3, in some cases, the heat generated in an abnormal state may not be uniformly applied to the fire extinguishing system, but rather locally applied to only certain areas. However, in order for the vaporizable substances inside the fire extinguishing system to vaporize rapidly and achieve a high-pressure state, the heat generated in the abnormal state must be uniformly applied to the fire extinguishing system. If a heat conduction layer is present, even if the heat generated in the abnormal state is applied locally, this heat can be quickly and evenly transferred to the fire extinguishing system, thereby enabling the fire extinguishing action of the fire extinguishing system to occur quickly and efficiently.
[0052] This specification discloses composite materials that can be present in the sealed space of the fire extinguishing system.
[0053] The term "composite material" refers to a material containing two or more components. Such a material may contain additional components, as long as it contains at least two components.
[0054] The composite material can exhibit an appropriate level of weight change rate. The weight change rate is the result of evaluation in accordance with "3. Weight Change Rate Evaluation" of this specification.
[0055] For example, the upper limit of the weight change rate of the composite material under a 10% strain pressure condition, as evaluated according to "3. Weight Change Rate Evaluation" above, may be approximately 3%, 2.8%, 2.6%, 2.4%, 2.2%, 2%, 1.8%, 1.6%, or 1.4%, and the lower limit may be approximately 0%, 0.5%, or 1%. The weight change rate may be within a range that is less than or equal to any one upper limit arbitrarily selected from the listed upper limits; or it may be greater than or equal to any one lower limit arbitrarily selected from the listed lower limits, while being less than or equal to any one upper limit arbitrarily selected from the listed upper limits. The lower the value of the weight change rate among the listed upper limits, the more appropriate it is.
[0056] The fact that the weight change rate is the same as described above means that the composite material appropriately contains the volatile substance described later, and maintains the volatile substance stably even when a certain level of stress is applied. Therefore, such a composite material can exhibit appropriate performance in the abnormal state.
[0057] To maintain the weight change rate at the aforementioned level, the components and ratios applied to the composite material can be controlled.
[0058] The composite material may contain a vaporizable substance. Such a vaporizable substance may, in some cases, be supported inside an inorganic gel and / or inorganic fiber, as described later. The term "vaporizable substance" refers to a substance that vaporizes at a predetermined temperature. Such a vaporizable substance can exist in liquid form at room temperature (25°C). Such a vaporizable substance can be used to reduce heat by heat exchange or the like in abnormal conditions of an object adjacent to the fire extinguishing device, or to remove flames generated by ignition and / or explosion. Such a vaporizable substance can rapidly vaporize in abnormal conditions to increase the pressure in a sealed space, open the vent area, and discharge to the outside through the opened vent area.
[0059] The vaporizable substance can be any substance that can be vaporized and is non-flammable, without any particular limitations. For example, the vaporizable substance can be a solvent having a predetermined range of freezing point and / or boiling point.
[0060] For example, the lower limit of the freezing point of the vaporized substance may be around -5°C, -4°C, -3°C, -2°C, -1°C, or 0°C, and the upper limit may be around 10°C, 9°C, 8°C, 7°C, 6°C, 5°C, 4°C, 3°C, or 2°C. The freezing point may be within a range that is less than or equal to any one upper limit arbitrarily selected from the listed upper limits; or within a range that is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits; or within a range that is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits, while being less than or equal to any one upper limit arbitrarily selected from the listed upper limits. The freezing point is the freezing point at 1 atmosphere.
[0061] For the vaporized substance to efficiently respond to abnormal conditions, it may be advantageous that it can be vaporized by the heat generated in the abnormal conditions, and for this purpose, the boiling point of the vaporized substance can be controlled.
[0062] The lower limit of the boiling point of the vaporized substance may be around 80°C, 85°C, 90°C, or 95°C, and the upper limit may be around 120°C, 115°C, 110°C, or 105°C. The boiling point may be within a range of less than or equal to any one upper limit arbitrarily selected from the listed upper limits; or within a range of greater than or equal to any one lower limit arbitrarily selected from the listed lower limits; or within a range of greater than or equal to any one lower limit arbitrarily selected from the listed lower limits, while being less than or equal to any one upper limit arbitrarily selected from the listed upper limits. The boiling point is the boiling point at 1 atmosphere.
[0063] As for the vaporizing substance, any suitable type can be selected and used without particular limitation, as long as it has a freezing point and / or boiling point within the aforementioned range and is non-flammable. A typical example of such a vaporizing substance is water, and accordingly, water can be used as the vaporizing substance, but the types of vaporizing substances that can be applied are not limited to those mentioned above.
[0064] The lower limit of the ratio of the volatile substance in the composite material may be, for example, around 40% by weight, 45% by weight, 50% by weight, 55% by weight, 60% by weight, 65% by weight, 70% by weight, 75% by weight, or 80% by weight, and the upper limit may be around 95% by weight, 90% by weight, 85% by weight, 80% by weight, 75% by weight, 70% by weight, 65% by weight, 60% by weight, 55% by weight, 50% by weight, 45% by weight, or 40% by weight. The ratio may be within a range where it is greater than or greater than any one lower limit arbitrarily selected from the listed lower limits; or within a range where it is greater than or greater than any one lower limit arbitrarily selected from the listed lower limits, and less than or equal to any one upper limit arbitrarily selected from the listed upper limits. By adjusting the content of the volatile substance, the desired properties such as the amount of heat absorbed can be achieved.
[0065] The aforementioned ratio is calculated assuming that the total weight of all substances present in the composite material is 100% by weight.
[0066] The composite material may contain additional components to ensure proper fire extinguishing function and the weight change rate.
[0067] The composite material may further include an inorganic gel and / or inorganic fibers. Such inorganic gel and / or inorganic fibers can cause the composite material to exhibit the aforementioned weight change rate characteristics and, if necessary, can play a role in supporting some or all of the components such as the aforementioned vaporizing substance.
[0068] The inorganic gel may be, for example, an oxide network formed by a so-called sol-gel process. Such an oxide network may include a network in which inorganic elements are linked by oxygen atoms. Examples of the inorganic elements include one or more selected from the group consisting of silicon, titanium, zirconium, niobium, tantalum, molybdenum, and tungsten. For example, if the inorganic element is silicon, the inorganic gel may be silica gel.
[0069] By controlling the density of the inorganic gel network, the functional groups, and their content, it is possible to achieve the desired weight change rate.
[0070] The lower limit of the ratio of the inorganic gel in the composite material may be, for example, around 0.1% by weight, 0.5% by weight, 1% by weight, 1.5% by weight, 2% by weight, 2.5% by weight, 3% by weight, 3.5% by weight, 4% by weight, 4.5% by weight, or 5% by weight, and the upper limit may be around 20% by weight, 19% by weight, 18% by weight, 17% by weight, 16% by weight, 15% by weight, 14% by weight, 13% by weight, 12% by weight, 11% by weight, 10% by weight, 9% by weight, 8% by weight, 7% by weight, 6% by weight, 5% by weight, 4% by weight, 3% by weight, or 2% by weight. The ratio may be greater than or greater than any one lower limit arbitrarily selected from the listed lower limits, and less than or less than any one upper limit arbitrarily selected from the listed upper limits. The ratio is calculated with the total weight of all substances present in the composite material set to 100% by weight.
[0071] In other examples, the lower limit of the content ratio of the inorganic gel to 100 parts by weight of the vaporizing substance may be approximately 1.5 parts by weight, 3 parts by weight, 5 parts by weight, 9.5 parts by weight, 10 parts by weight, 15 parts by weight, or 20 parts by weight, and the upper limit may be approximately 30 parts by weight, 25 parts by weight, 20 parts by weight, 15 parts by weight, 10 parts by weight, 5 parts by weight, 4 parts by weight, 3 parts by weight, or 2 parts by weight. The ratio may be within the range of being greater than or exceeding any one of the lower limits arbitrarily selected from the listed lower limits; or the ratio may be within the range of being greater than or exceeding any one of the lower limits arbitrarily selected from the listed lower limits, while being less than or equal to any one of the upper limits arbitrarily selected from the listed upper limits.
[0072] By including inorganic gels with appropriate networks and functional groups within the aforementioned range, it may be possible to achieve the desired weight change rate.
[0073] As the inorganic fibers, for example, inorganic fibers commonly used to form thermal insulation materials can be used, and examples of such are so-called glass fibers and / or ceramic fibers. Such inorganic fibers may exist, for example, in the form of woven fabrics or nonwoven fabrics. The category of woven fabrics or nonwoven fabrics may also include materials referred to as so-called paper, wool, or blankets.
[0074] For example, the inorganic fibers can include ceramic paper, ceramic paper with / with an inorganic binder, binder-free fibers, ceramic fiber, glass fiber, glass felt, basalt fiber, basalt felt, aramid fabric, silica felt, oxpan carbon felt, carbon fiber felt, and / or melamine fiber, and an organic binder can be used. When the inorganic fibers are used, they have excellent heat insulation properties and the sol absorbs moisture easily, so substances such as gels and heat absorbers can be uniformly positioned within the substrate, thereby increasing stability.
[0075] The properties of the inorganic fibers can be adjusted according to the purpose.
[0076] For example, the inorganic fiber may have a moisture retention range based on the ASTM-C 1511 standard. For example, the lower limit of the moisture retention may be around 55%, 56%, 57%, 58%, 59%, 60%, or 61%, and the upper limit may be around 100%, 95%, 90%, 85%, 80%, 75%, 70%, or 65%. The moisture retention can be evaluated using the method described in "8. Moisture Retention Evaluation" of the Examples section of this specification. The moisture retention may be within a range that is greater than or greater than any one lower limit arbitrarily selected from the listed lower limits; or within a range that is greater than or greater than any one lower limit arbitrarily selected from the listed lower limits, while being less than or equal to any one upper limit arbitrarily selected from the listed upper limits. By applying inorganic fibers with the above-described moisture retention, an appropriate weight change rate can be ensured.
[0077] The inorganic fibers can exhibit the aforementioned range of moisture absorption while contained within the composite material. Therefore, for example, if the inorganic fibers are contained within the composite material in the form of a woven or nonwoven fabric, the woven or nonwoven fabric can exhibit the aforementioned moisture absorption.
[0078] For example, the lower limit of the tensile strength of the inorganic fiber may be around 0.5, 1, 5, 10, 50, 70, 90, 95, or 100, and the upper limit may be around 500, 450, 400, 350, 300, 250, 200, 150, 100, 80, 60, 40, 20, 15, or 10. The tensile strength may be greater than or exceeding any one of the lower limits arbitrarily selected from the listed lower limits, and less than or equal to any one of the upper limits arbitrarily selected from the listed upper limits. The unit of the tensile strength is kPa.
[0079] For example, the lower limit of the compressive strength of the inorganic fiber may be around 1, 5, 8, 10, 50, 100, 110, 120, 130, 140, 145, or 150, and the upper limit may be around 500, 450, 400, 350, 300, 250, 200, 150, 100, 50, 40, 30, 20, 15, or 10. The compressive strength may be greater than or greater than any one lower limit arbitrarily selected from the listed lower limits, and less than or equal to any one upper limit arbitrarily selected from the listed upper limits. The unit of the compressive strength is kPa.
[0080] For example, the lower limit of the Young's modulus of the inorganic fiber may be around 0.1, 0.5, 1, 1.5, 2, 2.5, or 3, and its upper limit may be around 20, 18, 16, 14, 12, 10, 8, 6, or 4. The Young's modulus may be within a range where it is less than or equal to any one upper limit arbitrarily selected from the listed upper limits; or within a range where it is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits; or within a range where it is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits, and less than or equal to any one upper limit arbitrarily selected from the listed upper limits. The unit of the Young's modulus is MPa.
[0081] The inorganic fibers, when contained in the composite material, can exhibit one or more of the tensile strength, compressive strength, and Young's modulus within the specified range. Therefore, for example, if the inorganic fibers are contained in the composite material in the form of a woven or nonwoven fabric, the woven or nonwoven fabric can exhibit one or more of the tensile strength, compressive strength, and Young's modulus within the specified range. The tensile strength, compressive strength, and Young's modulus can be measured according to the KS K ISO 9073-3 standard.
[0082] By applying inorganic fibers exhibiting tensile strength, compressive strength, and / or Young's modulus within the aforementioned ranges, it is possible to form composite materials with the desired properties.
[0083] The lower limit of the density of the inorganic fiber may be approximately 0.01, 0.05, or 0.1, and the upper limit may be approximately 10, 8, 6, 4, 2, 1, 0.5, or 0.3. The density may be within a range where it is less than or equal to any one upper limit arbitrarily selected from the listed upper limits; or within a range where it is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits; or within a range where it is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits, and less than or equal to any one upper limit arbitrarily selected from the listed upper limits. The unit of density is g / cm³ 3 That is the case.
[0084] The inorganic fibers can exhibit the density within the specified range while contained within the composite material. Therefore, for example, if the inorganic fibers are contained within the composite material in the form of a woven or nonwoven fabric, the woven or nonwoven fabric can exhibit the density within the specified range.
[0085] If the inorganic fibers are included in the form of a woven or nonwoven fabric, the thickness of the woven or nonwoven fabric can be selected within a range that allows it to exhibit the aforementioned properties. For example, the lower limit of the thickness may be approximately 0.01 mm, 0.05 mm, 0.1 mm, 0.5 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, or 3 mm, and the upper limit may be approximately 100 mm, 50 mm, 30 mm, 10 mm, 8 mm, 6 mm, or 4 mm. The thickness may be within a range that is less than or equal to any one upper limit arbitrarily selected from the listed upper limits; or within a range that is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits; or within a range that is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits, while being less than or equal to any one upper limit arbitrarily selected from the listed upper limits.
[0086] The lower limit of the ratio of inorganic fibers in the composite material may be, for example, around 0.5% by weight, 1% by weight, 3% by weight, 5% by weight, 7% by weight, 9% by weight, 10% by weight, 15% by weight, or 20% by weight, and the upper limit may be around 60% by weight, 40% by weight, 30% by weight, 25% by weight, 20% by weight, 15% by weight, or 10% by weight. The ratio may be greater than or greater than any one lower limit arbitrarily selected from the listed lower limits, and less than or less than any one upper limit arbitrarily selected from the listed upper limits. The ratio is calculated with the total weight of all substances present in the composite material set to 100% by weight.
[0087] In other examples, the lower limit of the weight ratio of the inorganic fiber to 100 parts by weight of the vaporizing substance may be approximately 0.5 parts by weight, 1 part by weight, 5 parts by weight, 7 parts by weight, 7.5 parts by weight, 8 parts by weight, 8.5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, 50 parts by weight, 60 parts by weight, 70 parts by weight, or 75 parts by weight, and the upper limit may be approximately 100 parts by weight, 95 parts by weight, 90 parts by weight, 85 parts by weight, 80 parts by weight, 75 parts by weight, 70 parts by weight, 65 parts by weight, 60 parts by weight, 55 parts by weight, 50 parts by weight, 45 parts by weight, 40 parts by weight, 35 parts by weight, 30 parts by weight, 25 parts by weight, or 20 parts by weight. The ratio may be within a range where it is greater than or greater than any one lower limit arbitrarily selected from the listed lower limits, and less than or equal to any one upper limit arbitrarily selected from the listed upper limits.
[0088] When the inorganic fibers and inorganic gel are present simultaneously, the inorganic gel may be attached to the inorganic fibers, or the inorganic gel and inorganic fibers may be intertwined with each other. For example, by performing the gelation process in the presence of the inorganic fibers, as described later, the above-described structure can be realized, thereby enabling the composite material to more effectively perform the desired performance and function, such as the rate of weight change.
[0089] The composite material may further contain ionic compounds. Ionic compounds are compounds that can dissociate to form ions; examples include acids, bases, and salts.
[0090] The ionic compound may be a catalyst applied to form the inorganic gel, a freezing point modifier described later, or a carbonization catalyst. The ionic compound may be included in the composite material in an undissociated state, i.e., in a state without forming ions, or in a state in which it has dissociated and formed ions.
[0091] Ionic compounds play a crucial role in forming inorganic gels with the desired network structure and functional groups, and in ensuring that composite materials exhibit the desired effects over a wide temperature range.
[0092] As described later, inorganic gels can be formed by polymerizing metal alkoxides in the volatile substance (sol-gel process). The metal alkoxides have condensing functional groups, and such condensing functional groups usually exhibit polarity. Therefore, the density or polarity of the network structure of the inorganic gel formed by the polymerization of the alkoxide can be determined by the amount of remaining condensing functional groups. On the other hand, if ionic compounds are present, they can induce a so-called freezing point depression phenomenon in the volatile substance. The freezing point of the medium in which polymerization proceeds is related to the attractive forces between the constituent molecules of the medium and the energy of the molecules. Therefore, ionic compounds, in conjunction with the polymerization temperature, affect the polymerization efficiency, and the result is one of the factors that determine the density and degree of crosslinking of the inorganic gel network, as well as the amount of remaining condensing functional groups.
[0093] Furthermore, the freezing point determined by the addition of ionic compounds allows the composite material to stably exhibit the desired effect even at relatively low temperatures, and also allows for the determination of the carbonization layer formation efficiency of the carbonizable organic material, which will be discussed later.
[0094] For example, the ionic compound is ΔT of the following formula 1. f It can exist in an amount that falls within a predetermined range.
[0095] [Formula 1] △T f = K f × M × I
[0096] In Equation 1, K f is the freezing point depression constant of the vaporized substance, M is the molar concentration of the ionic compound relative to the vaporized substance, and I is the number of moles of ions generated when 1 mole of the ionic compound dissociates.
[0097] K in Equation 1f is the freezing point depression constant of the vaporizable substance, and its unit is K / m or °C / m. For example, when the vaporizable substance is water, the K f is 1.86.
[0098] M in Formula 1 is the molar concentration of the aforementioned freezing point adjuster, which is the molar concentration relative to the vaporizable substance. Accordingly, the aforementioned M is the number of moles of the ionic compound present per 1 kg of the vaporizable substance in the composite material.
[0099] I in Formula 1 is the number (moles) of ions that form 1 mole of the ionic compound when the ionic compound dissociates, and the dissociation at this time means a state where the freezing point adjuster is completely dissociated.
[0100] When two or more ionic compounds are present in the composite material, the aforementioned ΔT f is calculated for each compound, and the sum of these values is taken as the ΔT f value for the composite material.
[0101] ΔT in Formula 1 f may have a lower limit of, for example, about 5, 10, 15, 20 or 25, and an upper limit of about 50, 45, 40, 35, 30, 25, 20 or 15. The aforementioned ΔT f may be within a range that is greater than or equal to, or exceeds any one lower limit arbitrarily selected from the aforementioned listed lower limits; or within a range that is less than or equal to, or below any one upper limit arbitrarily selected from the aforementioned listed upper limits; or within a range that is simultaneously greater than or equal to, or exceeds any one lower limit arbitrarily selected from the aforementioned listed lower limits, and less than or equal to, or below any one upper limit arbitrarily selected from the aforementioned listed upper limits. ΔT in Formula 1 f has a unit of °C. When the content of the ionic compound is adjusted within the aforementioned range, the aforementioned object can be achieved.
[0102] In order for the ionic compound contained in the aforementioned content to exhibit an appropriate effect, the solubility of the ionic compound in the vaporizable substance (e.g., water) can be adjusted.
[0103] For example, the lower limit of solubility of the ionic compound in 100g of water at 25°C is 10g, 15g, 20g, 25g, 30g, 35g, 40g, 45g, 50g, 55g, 60g, 65g, 70g, 75g, 80g, 85g, 90g, 95g, 100g, 110g, 115g, 120g, 125g, 130g, 135g, 140g, 145g, 150g, 155g, 160g, 1 The amount may be around 65g, 170g, 175g, 180g, 185g, 190g, 195g, 200g, 205g, 210g, 215g, 225g, 230g, 235g, 240g, 255g, 260g, 265g, 270g, 275g, 280g, 285g, 290g, 295g, 300g, 305g, 310g, 315g, or 320g, with an upper limit of 1,000g or 900g. , 800g, 700g, 600g, 500g, 400g, 350g, 345g, 340g, 335g, 330g, 325g, 320g, 315g, 310g, 305g, 300g, 295g , 290g, 280g, 275g, 270g, 265g, 260g, 255g, 250g, 245g, 240g, 235g, 230g, 225g, 220g, 215g, 210g, 205g, The solubility may be approximately 200g, 195g, 190g, 185g, 180g, 175g, 170g, 165g, 160g, 155g, 150g, 145g, 140g, 135g, 130g, 125g, 120g, 115g, 110g, 105g, 100g, 95g, 90g, 85g, 80g, 75g, 70g, 65g, 60g, 55g, 50g, 45g, 40g, 35g, or 30g. The solubility is within the range of being greater than or exceeding any one of the lower limits arbitrarily selected from the listed lower limits; it may also be within the range of being greater than or exceeding any one of the lower limits arbitrarily selected from the listed lower limits, while being less than or equal to any one of the upper limits arbitrarily selected from the listed upper limits. The solubility is the weight (g) of the ionic compound that can be dissolved in 100g of water at 25°C. The solubility can be evaluated using the method described in "7. Solubility Evaluation" of the Examples section of this specification.
[0104] The lower limit of the solubility of the ionic compound in 100g of water at 0°C may be approximately 10g, 15g, 20g, 25g, 30g, 35g, 40g, 45g, 50g, 55g, 60g, 65g, 70g, 75g, 80g, 85g, 90g, 95g, 100g, 110g, 115g, 120g, 125g, 130g, 135g, 140g, 145g, 150g, 155g, 160g, 165g, 170g, 175g, 180g, 185g, 190g, 195g, 200g, 205g, 210g, or 215g, and the upper limit may be approximately 1,000g, 900g, 8 00g, 700g, 600g, 500g, 400g, 300g, 250g, 245g, 240g, 235g, 230g, 225g, 220g, 215g, 210g, 205g, 200g, 195g, 190g, 185g, 180g, 175g, 170g, 165g, 160g, 155g, 150g, 145g, 140g, 135g, 130g, 125g, 120g, 115g, 110g, 105g, 100g, 95g, 90g, 85g, 80g, 75g, 70g, 65g, 60g, 55g, 50g, 45g, 40g, or even around 35g or 30g. The solubility is within a range that is greater than or greater than any one lower limit arbitrarily selected from the listed lower limits; or it may be within a range that is greater than or greater than any one lower limit arbitrarily selected from the listed lower limits, and less than or less than any one upper limit arbitrarily selected from the listed upper limits. The solubility is the weight (g) of the ionic compound that can be dissolved in 100g of water at 0°C. The solubility can be evaluated by the method described in "7. Solubility Evaluation" of the Examples section of this specification.
[0105] The type of ionic compound is determined according to the purpose and is not particularly limited. For example, examples of ionic compounds having a freezing point depression effect include one or more selected from the group consisting of formate salts, acetate salts, carbonates, and sulfates. Specifically, for example, one or more substances consisting of sodium acetate (CH3COONa), sodium formate (HCOONa), potassium acetate (CH3COOK), potassium formate (HCOOK), calcium formate ((HCOO)2Ca), magnesium formate ((HCOO)2Mg), potassium carbonate (K2CO3), and ammonium sulfate ((NH4)2SO4) can be used as the ionic compound.
[0106] For example, the lower limit of the amount of an ionic compound applied to adjust the freezing point relative to 100 parts by weight of the vaporized substance may be approximately 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, or 55 parts by weight, and the upper limit may be approximately 200, 150, 100, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, or 30 parts by weight. The ratio may be greater than or greater than any one of the lower limits arbitrarily selected from the listed lower limits, and less than or equal to any one of the upper limits arbitrarily selected from the listed upper limits.
[0107] If other ionic compounds (for example, ionic compounds used as carbonization catalysts, as described later, or acids and bases added for the formation of inorganic gels) are added to the composite material in addition to the freezing point modifier, then all ionic compounds present in the composite material will be ΔT in Equation 1. f It can be present in an amount that falls within the predetermined range.
[0108] The composite material may include a carbonization catalyst and a carbonizable organic substance as additional components. The combination of components ensures that carbides of the carbonizable organic substance are formed at the required time (e.g., the abnormal state). These formed carbides can block heat transfer. The carbonization catalyst can promote the carbonization of the carbonizable organic substance. The carbonization catalyst forms acids or acidic salts or ions at high temperatures, and these components can promote the carbonization and gas generation processes. Depending on the type of carbonization catalyst, it may impart flame retardancy to the carbides or form components that exhibit flame retardancy on their own. For example, the carbonization catalyst may form phosphoric acid-based substances through decomposition at high temperatures, and these substances can polymerize to become flame retardant. This allows the carbonization catalyst to be included in the composite material, enabling the composite material to effectively respond to abnormal states.
[0109] The carbonization catalyst and the carbonizable organic matter must be applied together with the vaporizable substance, and in this case, the carbonization catalyst used must have a solubility of a certain level or higher in the vaporizable substance (e.g., water). That is, the components dispersed in the vaporizable substance can come into contact with each other more effectively at the necessary time and interact to efficiently form the desired carbides, etc. Furthermore, by adjusting the solubility of the carbonization catalyst in the vaporizable substance, aggregation and phase separation phenomena of the components cannot occur within the composite material, and the formation of the carbides and / or the flame retardant can be promoted more effectively. For example, the lower limit of the solubility of the carbonization catalyst in the vaporized substance or water may be around 5g, 10g, 15g, 20g, 25g, 30g, 35g, or 40g, and the upper limit may be around 1000g, 900g, 800g, 700g, 600g, 500g, 400g, 300g, 200g, 100g, 90g, 80g, 70g, 60g, 50g, 40g, or 30g. The solubility may be within a range that is greater than or greater than any one lower limit arbitrarily selected from the listed lower limits; or within a range that is greater than or greater than any one lower limit arbitrarily selected from the listed lower limits, and less than or equal to any one upper limit arbitrarily selected from the listed upper limits. The solubility is the weight (g) of the carbonization catalyst that can be dissolved in 100g of the solvent (e.g., water) at 25°C. The solubility is measured by the method described in "7. Solubility Evaluation" of the Examples section of this specification.
[0110] The carbonization catalyst can be used without particular limitations as long as it can be decomposed at high temperatures to form an acid or an acidic salt or ion, and has the aforementioned solubility. Examples of the carbonization catalyst include phosphoric acid, phosphate compounds such as phosphates, phosphonate compounds, or phosphate compounds. The carbonization catalyst may be, for example, primary or secondary ammonium phosphate, urea phosphate, guanylurea phosphate, or polyammonium phosphate, and one or more of these can be selected and used.
[0111] The carbonization catalyst can be present in an appropriate content considering the desired effect. For example, the lower limit of the weight ratio of the carbonization catalyst to 100 parts by weight of the vaporizable substance is 0.01 parts by weight, 0.05 parts by weight, 0.1 parts by weight, 0.5 parts by weight, 1 part by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight, 4 parts by weight, 5 parts by weight, 5.5 parts by weight, 6 parts by weight, 6.5 parts by weight, 7 parts by weight, 7.5 parts by weight, 8 parts by weight, 10 parts by weight, 20 parts by weight, 30 parts by weight, 40 parts by weight, 50 parts by weight, and 100 parts by weight. The amount may be approximately 1,000 parts, 900 parts, 800 parts, 700 parts, 600 parts, 500 parts, 100 parts, 50 parts, 400 parts, 10 parts, or 5 parts. The upper limit may be approximately 1,000 parts, 900 parts, 800 parts, 700 parts, 600 parts, 500 parts, 400 parts, 100 parts, 50 parts, 40 parts, 30 parts, 20 parts, 15 parts, 10 parts, or 5 parts. The ratio may be within a range that is less than or equal to any one upper limit arbitrarily selected from the listed upper limits; or within a range that is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits; or within a range that is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits, while being less than or equal to any one upper limit arbitrarily selected from the listed upper limits. If the content of the carbonization catalyst is excessively high, the content of the vaporizable substance that can be applied to the composite material will be limited, and the vaporization characteristics of the vaporizable substance will be affected by the carbonization catalyst, making it difficult to secure the desired properties. Therefore, the amount of the carbonization catalyst can be adjusted with this in mind.
[0112] The carbonizable organic matter is an organic substance that carbonizes and forms a carbide when exposed to a flame or heat at a predetermined temperature. The carbide formed by such an organic substance is often porous, and therefore can have an insulating function. Thus, when the composite material is exposed to abnormal heat generation, ignition, or explosion, the organic substance can form an appropriate carbide and exhibit an insulating function. As described above, by adding the specific carbonization catalyst and the carbonizable organic matter to a vaporized substance, it is possible to form a carbide that can effectively respond to abnormal heat generation, ignition, and / or explosion, even when a small amount of the carbonizable organic matter is applied.
[0113] The aforementioned organic material can be any suitable type without particular limitations, as long as it is a substance that forms char when exposed to heat or flame.
[0114] Examples of such organic substances include sugars such as sorbitol and mannitol, polysaccharides such as starch or dextrins (e.g., maleated cyclodextrin and metal salts of MC), polyhydric alcohols such as pentaerythritol, dipentaerythritol, tripentaerythritol, or THEIC (tris(hydroxyethyl)isocyanurate), cellulose, BSPPO (bi(4-methoxy-1-phospha-2,6,7-trioxabicyclo[2.2.2]-octan-1-sulfide)phenylphosphate), lignin (alkali lignin and urea-modified liginin, etc.), and methylol melamine. Examples include, but are not limited to, melamine compounds such as melamine, phenol-formaldehyde resins, and / or char-forming polymers such as PA6T (Poly-hexa methylene terephthalamide).
[0115] A typical example of a carbonizable organic substance is starch. Starch is relatively easy to obtain and can form suitable carbonized materials when exposed to heat or flame.
[0116] The type of starch can be adjusted in order to efficiently form the aforementioned char and to ensure that the formed char effectively exhibits the desired fire-extinguishing or heat-insulating effect.
[0117] For example, the starch can be a starch containing amylose and amylopectin, in which their ratio is adjusted to an appropriate level. As is well known, amylopectin and amylose are types of polysaccharides mainly found in plants, and starch, among polysaccharides, is composed of amylose and amylopectin. Amylose is composed of glucose molecules linked by α(1→4) glycosidic bonds and has a linear structure, while amylopectin has relatively short, highly branched chains. Amylose crystallizes relatively easily compared to amylopectin, and amylopectin has relatively higher solubility in water compared to amylose.
[0118] By using starch containing amylose and amylopectin having the aforementioned properties in an appropriate ratio, the desired composite material can be provided more efficiently.
[0119] For example, in the starch containing amylose and amylopectin, the lower limit of the weight ratio of amylopectin to 100 parts by weight of amylose may be around 150 parts by weight, 200 parts by weight, 250 parts by weight, or 300 parts by weight, and the upper limit may be around 900 parts by weight, 850 parts by weight, 800 parts by weight, 750 parts by weight, 700 parts by weight, 650 parts by weight, 600 parts by weight, 550 parts by weight, 500 parts by weight, 450 parts by weight, 400 parts by weight, 350 parts by weight, or 300 parts by weight. The ratio may be within a range where it is less than or equal to any one upper limit arbitrarily selected from the listed upper limits; or within a range where it is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits; or within a range where it is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits, and less than or equal to any one upper limit arbitrarily selected from the listed upper limits. The ratio of amylose to amylopectin can be measured according to the method described in "5. Measurement of Amylopectin and Amylose Content" in the Examples section of this specification.
[0120] As the starch, a starch having a molecular weight, for example, a weight-average molecular weight (Mw), within a predetermined range can be used. For example, the lower limit of the weight-average molecular weight of the starch is 200,000, 250,000, 300,000, 350,000, 400,000, 450,000, 500,000, 550,000, 600,000, 650,000, 700,000, 750,000, 800,000, 850,000, 900,000, 950,000. 00, 1,000,000, 1,500,000, 2,000,000, 2,500,000, 3,000,000, 3,500,000, 4,000,000, 4,500,000, 5,000,000, 5,500,000, 6,000,000, 6,500,000, 7,000,000, 7,500,000, 8,000 It may be around 1,000, 8,500,000, 9,000,000, 9,500,000, 10,000,000, 20,000,000, 30,000,000, 40,000,000 or 50,000,000, with the upper limit being 1,000,000,000, 900,000,000, 800,000,000, and 700 The molecular weight may be approximately ,000,000, 600,000,000, 500,000,000, 400,000,000, 300,000,000, 200,000,000, 150,000,000, 100,000,000, 90,000,000, 80,000,000, 70,000,000, or 60,000,000. The molecular weight may be within a range where it is less than or equal to any one upper limit arbitrarily selected from the listed upper limits; or within a range where it is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits; or within a range where it is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits, and less than or equal to any one upper limit arbitrarily selected from the listed upper limits. Starch having the aforementioned molecular weight (Mw) can more effectively form carbides that have the desired function (e.g., heat insulation) when exposed to heat or flame. The molecular weight can be measured by the method described in "4. Molecular Weight Measurement" of the Examples section of this specification. The unit of the molecular weight is g / mol.
[0121] The carbonizable organic material (for example, the starch) can be one having a gelatinization viscosity within a certain range. Such gelatinization viscosity is related to the properties of the carbonizable organic material when present in a vaporized substance, and by controlling the gelatinization viscosity, carbides can be formed more effectively. The lower limit of the gelatinization viscosity of the carbonizable organic matter (e.g., starch) may be around 150, 200, 250, 300, 350, 400, 450, 500, 550, 650, 700, 750, 800, 850, 900, 950, or 1,000, and the upper limit may be around 5,000, 4,500, 4,000, 3,500, 3,000, 2,500, 2,000, 1,500, 1,000, 950, 900, 850, 800, 750, 700, 650, 600, 550, 500, 450, 400, 350, or 300. The gelatinization viscosity may be within a range where it is less than or equal to any one upper limit arbitrarily selected from the listed upper limits; or within a range where it is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits; or within a range where it is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits, and less than or equal to any one upper limit arbitrarily selected from the listed upper limits. The unit of the gelatinization viscosity is BU (Brabeder unit).
[0122] The lower limit of the weight ratio of the carbonizable organic matter to 100 parts by weight of the vaporizable substance may be approximately 0.001 parts by weight, 0.005 parts by weight, 0.01 parts by weight, 0.05 parts by weight, 0.1 parts by weight, 0.5 parts by weight, 1 part by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight, 4 parts by weight, 4.5 parts by weight, 5 parts by weight, 5.5 parts by weight, or 6 parts by weight, and the upper limit may be approximately 50 parts by weight, 45 parts by weight, 40 parts by weight, 35 parts by weight, 30 parts by weight, 25 parts by weight, 20 parts by weight, 15 parts by weight, 10 parts by weight, 5 parts by weight, 4 parts by weight, 3 parts by weight, 2 parts by weight, or 1 part by weight. The ratio may be within a range where it is less than or equal to any one upper limit arbitrarily selected from the listed upper limits; or within a range where it is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits; or within a range where it is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits, while being less than or equal to any one upper limit arbitrarily selected from the listed upper limits. Carbonizable organic matter included in such a ratio allows the composite material to effectively form carbides when needed, and can have excellent overall handling and storage stability.
[0123] The composite material may include an absorbent polymer as an optional additional component. The absorbent polymer is a polymer that has the property of absorbing water.
[0124] In one example, the superabsorbent polymer may be a so-called hydrogel polymer or hydrogel, generally defined as a crosslinked hydrophilic polymer. Such polymers are also known as SAPs (Super Absorbent Polymers).
[0125] The aforementioned superabsorbent polymer is a material capable of absorbing tens to thousands of times its own weight in water. Such a material can serve to ensure that the composite material exists in a gel state as a whole, thereby ensuring handling and storage stability.
[0126] There are no particular restrictions on the type of superabsorbent polymer; generally, any polymer that can be applied as a SAP can be used without limitation.
[0127] Typically, the material used is a polyacrylate-based vinyl polymer. The polyacrylate-based polymer is a polymer made from acrylate monomers, and if necessary, other copolymers can be added to form the polymer.
[0128] The superabsorbent polymer may, in one example, be a particulate polymer. By applying the superabsorbent polymer, the weight-based size distribution of the particulate superabsorbent polymer can be controlled in order to ensure the desired viscosity characteristics and fire extinguishing function. In this specification, the term "weight-based size distribution of superabsorbent polymer" refers to a size distribution measured according to the EDANA WSP 220.3 standard, where the sample of particulate superabsorbent polymer is divided into fractions with a size of less than 150 μm (hereinafter referred to as "fraction A"), fractions in the range of 150 μm to 300 μm (hereinafter referred to as "fraction B"), fractions in the range of 300 μm to 600 μm (hereinafter referred to as "fraction C"), fractions in the range of 600 μm to 850 μm (hereinafter referred to as "fraction D"), and fractions exceeding 850 μm (hereinafter referred to as "fraction E"), and the weight of each fraction is expressed as a percentage (weight ratio of each fraction) of the total weight of the particulate superabsorbent polymer sample.
[0129] The particulate superabsorbent polymer may have a maximum weight size in the weight-based size distribution that falls within the range of 150 μm to 850 μm. In the above, the maximum weight size is the size of the fraction that shows the highest weight ratio among the weight ratios of fraction A, fraction B, fraction C, fraction D, and fraction E. That is, the fact that the maximum weight size is within the range of 150 μm to 850 μm means that the weight ratio of the particulate superabsorbent polymer belonging to one or more of fractions B, C, and D is the largest. The weight ratios of two fractions may be the same, and that weight ratio may be the highest among the weight ratios of all fractions, so there may be one or more fractions with the maximum weight size. In one example, the fraction with the maximum weight size may be fraction C among fractions B, C, and D. Therefore, the maximum weight size in the weight-based size distribution may fall within the range of 300 μm to 600 μm.
[0130] In the weight-based size distribution of the particulate superabsorbent polymer, the lower limit of the weight ratio in the fraction showing the maximum weight size (i.e., the weight ratio of the superabsorbent polymer belonging to the maximum weight size in the weight-based size distribution) may be approximately 35% by weight, 40% by weight, 45% by weight, 50% by weight, 55% by weight, 60% by weight, 65% by weight, 70% by weight, 71% by weight, 72% by weight, 73% by weight, or 74% by weight, and the upper limit may be approximately 95% by weight, 90% by weight, 85% by weight, 80% by weight, 79% by weight, 78% by weight, 77% by weight, 76% by weight, or 75% by weight. The weight ratio may be within a range that is greater than or greater than any one of the lower limits arbitrarily selected from the listed lower limits; or within a range that is greater than or greater than any one of the lower limits arbitrarily selected from the listed lower limits, and less than or equal to any one of the upper limits arbitrarily selected from the listed upper limits.
[0131] If the maximum weight size is excessively small, and / or the weight ratio in the fraction representing the maximum weight size is excessively small, the composite material may not be able to properly form the desired gel, potentially leading to reduced handling and storage properties, or failure to exhibit the desired fire extinguishing function. Therefore, an appropriate particulate water-absorbing polymer can be selected with this in mind.
[0132] If included, the lower limit of the weight ratio of the superabsorbent polymer to 100 parts by weight of the vaporizing substance may be approximately 0.01 parts by weight, 0.5 parts by weight, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, or 9 parts by weight, and the upper limit may be approximately 50 parts by weight, 45 parts by weight, 40 parts by weight, 35 parts by weight, 30 parts by weight, 29 parts by weight, 28 parts by weight, 27 parts by weight, 26 parts by weight, 25 parts by weight, 24 parts by weight, 23 parts by weight, 22 parts by weight, 21 parts by weight, 20 parts by weight, 19 parts by weight, 18 parts by weight, 17 parts by weight, 16 parts by weight, 15 parts by weight, 14 parts by weight, 13 parts by weight, 12 parts by weight, 11 parts by weight, 10 parts by weight, 9 parts by weight, 8 parts by weight, 7 parts by weight, 6 parts by weight, 5 parts by weight, 4 parts by weight, 3 parts by weight, or 2 parts by weight. The ratio may be within a range where it is less than or equal to any one upper limit arbitrarily selected from the listed upper limits; or within a range where it is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits; or within a range where it is greater than or equal to any one lower limit arbitrarily selected from the listed lower limits, and less than or equal to any one upper limit arbitrarily selected from the listed upper limits.
[0133] The sealed space or composite material inside the fire extinguishing device may contain the aforementioned components and, if necessary, additional components.
[0134] This specification discloses a method for manufacturing the composite material.
[0135] For example, the manufacturing method may include a step of polymerizing the precursor solution containing the inorganic gel precursor and the vaporizing substance.
[0136] The polymerization described above is a process in which relatively low molecular weight substances, such as monomers or oligomers, form a network to form high molecular weight components. In this case, the monomer or oligomer may be the precursor. Furthermore, there are no particular restrictions on the specific method by which the polymerization is carried out. For example, if the inorganic gel precursor is a condensing precursor described later, the polymerization process may be a so-called sol-gel process.
[0137] As the precursor, for example, a metal alkoxide can be used. Such a precursor is a condensation precursor and can form an inorganic gel via the sol-gel process. Specifically, examples of the metal alkoxide include one or more alkoxides selected from the group consisting of silicon, titanium, zirconium, niobium, tantalum, molybdenum, and tungsten. The lower limit of the number of carbon atoms in the alkoxide may be around 4, 6, 8, or 10, and the upper limit may be around 20, 18, 16, 14, 12, 10, or 8. The number of carbon atoms may be within a range that is greater than or exceeds any one of the lower limits arbitrarily selected from the listed lower limits, and less than or equal to any one of the upper limits arbitrarily selected from the listed upper limits. As the precursor, for example, a component called so-called water glass (sodium silicate) can be used, and such a component can form silica gel as an inorganic gel.
[0138] As the aforementioned vaporizing substance, components such as water can be used.
[0139] The composition of the precursor solution can be adjusted to form the desired inorganic gel and composite material.
[0140] For example, the content of the vaporized substance in the precursor solution can be adjusted. For example, the lower limit of the content of the vaporized substance in the precursor solution may be around 30% by weight, 40% by weight, 50% by weight, 60% by weight, or 65% by weight, and the upper limit may be around 95% by weight, 90% by weight, 85% by weight, 80% by weight, 75% by weight, 70% by weight, 65% by weight, or 60% by weight. The content may be greater than or greater than any one lower limit arbitrarily selected from the listed lower limits, and less than or equal to any one upper limit arbitrarily selected from the listed upper limits.
[0141] In the precursor solution, the lower limit of the weight ratio of the precursor to 100 parts by weight of the vaporizable substance may be approximately 0.001 parts by weight, 0.005 parts by weight, 0.01 parts by weight, 0.05 parts by weight, 0.1 parts by weight, 0.15 parts by weight, 0.2 parts by weight, 0.25 parts by weight, 0.3 parts by weight, 0.4 parts by weight, 0.5 parts by weight, 1 part by weight, 3 parts by weight, 5 parts by weight, 10 parts by weight, 15 parts by weight, or 20 parts by weight, and the upper limit may be approximately 25 parts by weight, 20 parts by weight, 15 parts by weight, 10 parts by weight, 5 parts by weight, 4 parts by weight, 3 parts by weight, 2 parts by weight, 1 part by weight, or 0.5 parts by weight. The content may be greater than or greater than any one lower limit arbitrarily selected from the listed lower limits, and less than or equal to any one upper limit arbitrarily selected from the listed upper limits.
[0142] The precursor solution can be composed to exhibit a pH within a predetermined range. For example, the lower limit of the pH of the precursor solution may be around 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, or 7, and the upper limit may be around 14, 13, 12, 11, 10, 9, 8, or 7. The pH may be within a range where it is above or above any one lower limit arbitrarily selected from the listed lower limits, and below or below any one upper limit arbitrarily selected from the listed upper limits.
[0143] To adjust the pH, the precursor solution may further contain a catalyst. Such a catalyst may be one of the ionic compounds mentioned above. There are no particular restrictions on the type of catalyst that can be applied; for example, acid catalysts or base catalysts applicable to general sol-gel processes can be used. Examples of such acid catalysts include one or more selected from hydrochloric acid, sulfuric acid, sulfuric acid fluoride, nitric acid, phosphoric acid, acetic acid, hexafluorophosphate, p-toluenesulfonic acid, and trifluoromethanesulfonic acid, while examples of base catalysts include, but are not limited to, alkaline catalysts such as sodium hydroxide, ammonium hydroxide, or ammonium chloride.
[0144] The content of the catalyst can be controlled within a range that allows the aforementioned pH to be achieved. For example, in the precursor solution, the lower limit of the molar concentration of the catalyst relative to the vaporizable substance (i.e., the number of moles of catalyst present per 1 kg of vaporizable substance) may be around 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.5, 1, or 1.5, and the upper limit may be around 5, 4.5, 4, 3.5, 3, 2.5, 2, 1.5, 1, 0.8, 0.6, or 0.4. The molar concentration may be greater than or greater than any one lower limit arbitrarily selected from the listed lower limits, and less than or equal to any one upper limit arbitrarily selected from the listed upper limits.
[0145] The precursor solution may additionally contain ionic compounds in addition to the catalyst. Such ionic compounds can be added to adjust the molecular energy or intermolecular forces of the vaporizing substance, as described above, in order to form the desired inorganic gel. Examples of ionic compounds include the aforementioned freezing point adjusters or carbonization catalysts.
[0146] The content of all ionic compounds present in the precursor solution, including the catalyst, can be adjusted. Such adjustment of content controls the fluidity of the vaporized substance, and this controlled fluidity affects the polymerization efficiency of the precursor, allowing the desired inorganic gel to be formed at a specified polymerization temperature.
[0147] For example, the ionic compound is ΔT of the above formula 1. f It can be added such that it falls within the aforementioned predetermined range.
[0148] The precursor solution may contain any other necessary components besides those mentioned above. For example, the polymerization can be carried out in the presence of the inorganic fibers. The inorganic fibers also affect the polymerization efficiency of the precursor. In such cases, the precursor solution may contain the inorganic fibers mentioned above.
[0149] The lower limit of the weight ratio of the inorganic fiber to 100 parts by weight of the vaporizable substance in the precursor solution may be approximately 0.5 parts by weight, 1 part by weight, 5 parts by weight, 7 parts by weight, 7.5 parts by weight, 8 parts by weight, 8.5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, 50 parts by weight, 60 parts by weight, 70 parts by weight, or 75 parts by weight, and the upper limit may be approximately 100 parts by weight, 95 parts by weight, 90 parts by weight, 85 parts by weight, 80 parts by weight, 75 parts by weight, 70 parts by weight, 65 parts by weight, 60 parts by weight, 55 parts by weight, 50 parts by weight, 45 parts by weight, 40 parts by weight, 35 parts by weight, 30 parts by weight, 25 parts by weight, or 20 parts by weight. The weight ratio may be within a range where it is greater than or exceeds any one of the lower limits arbitrarily selected from the listed lower limits, and at the same time less than or equal to any one of the upper limits arbitrarily selected from the listed upper limits.
[0150] The temperature for polymerization of the precursor solution can be controlled. Such a controlled temperature is ΔT f It works in conjunction with ionic compounds having a specific value to contribute to the formation of inorganic gels in the desired form.
[0151] For example, the lower limit of the polymerization temperature may be around 10°C, 15°C, 20°C, 25°C, 30°C, or 35°C, and the upper limit may be around 50°C, 45°C, 40°C, 35°C, 30°C, or 25°C. The polymerization temperature may be at or above any one of the lower limits arbitrarily selected from the listed lower limits, while simultaneously being below or below any one of the upper limits arbitrarily selected from the listed upper limits.
[0152] For the formation of the target composite material, polymerization of the precursor or the prepolymer of the precursor can be carried out in the presence of inorganic fibers. For this purpose, the polymerization can proceed in multiple stages. For example, the production method may include a first stage (primary polymerization) in which the precursor solution is polymerized to obtain a prepolymer, and a second stage (secondary polymerization) in which the precursor or prepolymer is polymerized in the presence of inorganic fibers to obtain an inorganic gel. The precursor solution applied to the primary polymerization does not have to contain the inorganic fibers. That is, the primary polymerization is carried out without inorganic fibers, and the second stage secondary polymerization can be carried out in the presence of inorganic fibers. That is, after primary polymerization, the polymer can be mixed with inorganic fibers and polymerization can proceed further. The precursor in the second stage may mean a precursor that did not participate in polymerization and form a prepolymer during primary polymerization.
[0153] The primary polymer or prepolymer may be, for example, an inorganic sol.
[0154] The polymerization temperature, polymerization time, and / or mixing conditions of the first stage can be adjusted.
[0155] The lower limit of the polymerization temperature in the first stage may be approximately 10°C, 15°C, 20°C, 25°C, 30°C, or 35°C, and the upper limit may be approximately 50°C, 45°C, 40°C, 35°C, 30°C, or 25°C. The polymerization temperature may be at or above any one of the lower limits arbitrarily selected from the listed lower limits, while simultaneously being below or below any one of the upper limits arbitrarily selected from the listed upper limits.
[0156] The first step can be carried out while stirring the precursor solution at an appropriate speed. In this process, the lower limit of the stirring speed may be around 100 rpm, 150 rpm, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, or 500 rpm, and the upper limit may be around 2,000 rpm, 1,500 rpm, 1,000 rpm, 800 rpm, 600 rpm, 400 rpm, or 300 rpm. The stirring speed may be greater than or greater than any one lower limit arbitrarily selected from the listed lower limits, and less than or equal to any one upper limit arbitrarily selected from the listed upper limits.
[0157] The lower limit of the time for the primary polymerization may be approximately 1 second, 5 seconds, 10 seconds, 30 seconds, 1 minute, 5 minutes, 10 minutes, or 15 minutes, and the upper limit may be approximately 60 minutes, 55 minutes, 50 minutes, 45 minutes, 40 minutes, 35 minutes, 30 minutes, 25 minutes, 20 minutes, 15 minutes, 10 minutes, 8 minutes, 6 minutes, 4 minutes, 2 minutes, 1 minute, or 30 seconds. The time may be greater than or greater than any one lower limit arbitrarily selected from the listed lower limits, and less than or less than any one upper limit arbitrarily selected from the listed upper limits.
[0158] By forming a primary polymer (prepolymer or a mixture of prepolymer and precursor) under the above conditions and proceeding with secondary polymerization, the desired composite material can be formed.
[0159] The primary polymer can be further subjected to secondary polymerization to form an inorganic gel. As mentioned above, secondary polymerization can be carried out in the presence of the inorganic fibers. That is, after primary polymerization, the inorganic fibers and the primary polymer can be mixed to satisfy the aforementioned ratio (ratio of inorganic fibers to 100 parts by weight of vaporizable substance), and then polymerization can be further carried out to effectively form the desired inorganic gel.
[0160] The aforementioned secondary polymerization can be carried out at an appropriate temperature.
[0161] For example, the lower limit of the polymerization temperature may be around 10°C, 15°C, 20°C, or 25°C, and the upper limit may be around 40°C, 35°C, 30°C, or 25°C. The temperature may be within a range where it is above or above any one of the lower limits arbitrarily selected from the listed lower limits, and below or below any one of the upper limits arbitrarily selected from the listed upper limits.
[0162] By maintaining the mixture of the primary polymer and inorganic fibers at the aforementioned temperature during secondary polymerization, the desired inorganic gel can be obtained.
[0163] The inorganic gel formed in this manner can be mixed with other components of the required composite material to produce the composite material. The components may be mixed with the inorganic gel after its production, or mixed into a precursor solution before the inorganic gel is produced, or at an appropriate point during the inorganic gel production process.
[0164] After manufacturing the composite material, it can be inserted into a case to form a fire extinguishing device. Alternatively, the entire or partial manufacturing process of the composite material can be carried out within the case to form a fire extinguishing device. For example, the fire extinguishing device and the composite material can be manufactured simultaneously by pre-arranging inorganic fibers in the case, injecting a primary polymer, performing additional polymerization, and introducing additional components as needed after polymerization.
[0165] This specification also discloses electronic equipment or devices to which the fire extinguishing system is applied.
[0166] The type of electronic equipment or device is not particularly limited. For example, the composite material or fire extinguishing device can be applied to equipment or devices that pose a risk of abnormal heat generation, ignition, and / or explosion during operation, maintenance, and / or storage, and where such abnormal phenomena should be controlled.
[0167] A typical example of the aforementioned equipment or device is a battery. In particular, in battery modules composed of multiple battery cells, it is important to prevent abnormal heat generation, ignition, and / or explosion occurring in one battery cell from spreading to other adjacent battery cells.
[0168] This specification discloses a battery module including the fire extinguishing device.
[0169] Such a battery module may essentially include a number of battery cells; and the fire extinguishing device positioned between the battery cells.
[0170] As long as the fire extinguishing device is applied, the specific configuration of the battery module, such as the type of battery cell, is not particularly limited, and known materials can be used. For example, known pouch-type, rectangular, or cylindrical battery cells can be used as the battery cells.
[0171] The method for manufacturing the battery module is not particularly limited. For example, a method can be used in which a fire extinguishing device similar in form to a battery cell is manufactured as described above, and then the fire extinguishing device is positioned at the required location during the manufacturing process of the battery module. [Effects of the Invention]
[0172] This specification discloses composite materials and fire extinguishing devices that can be applied to products or elements that are in or potentially in an abnormal state and can effectively respond to said abnormal state. For example, the composite materials, etc., can be applied to an article containing multiple such products or elements and can respond to abnormal heat generation, explosion, and ignition occurring in any one of the elements or products, and can prevent or minimize the propagation of such heat generation, explosion, and ignition to adjacent elements or products. The composite materials, etc., also exhibit excellent handling and storage stability. This specification can also provide applications for the composite materials, etc. [Brief explanation of the drawing]
[0173] [Figure 1] This is an exemplary cross-sectional view of a battery module to which a fire extinguishing system has been applied. [Figure 2] This is an illustrative diagram illustrating the operating principle of a fire extinguishing system. [Figure 3] This is an illustrative diagram illustrating the operating principle of a fire extinguishing system. [Figure 4] This diagram illustrates the process of manufacturing a fire extinguishing device in an example. [Modes for carrying out the invention]
[0174] The composite materials, etc. will be described in detail below through examples and comparative examples, but the scope of the composite materials, etc. is not limited by the following examples.
[0175] 1. Convection Exam The composite material is placed on an aluminum dish to a thickness of 3 mm. The aluminum dish used is one with a thickness of approximately 0.2 mm. A temperature sensor (K-type thermocouple, Fluke IR thermometers model 566) is positioned on the side of the aluminum dish opposite to the side where the composite material is present, and the temperature is measured using the temperature sensor while a flame is applied towards the composite material. The flame is applied vertically to the aluminum dish from a distance of approximately 1 inch using two cans of butane gas (220 g capacity can-type butane gas (unused product)) and a torch. The temperature is measured using the temperature sensor while the flame is applied for about 3 minutes, and evaluated according to the following criteria.
[0176] <Evaluation Criteria> Pass: If the temperature sensor's measured temperature is maintained below 250°C. NG: If the temperature sensor measures a temperature of 250°C or higher, or if the aluminum dish is observed to melt within 35 seconds.
[0177] 2. Chain reaction test Rectangular batteries were arranged at intervals of approximately 3 mm, with a fire extinguishing device positioned between them. CATL products (120Ah, 3.2V, size = thickness × width × length = 48 × 174 × 165 mm) were used as the rectangular batteries, and the batteries were applied to the test in a 100% charged state. In the above arrangement, battery ignition was induced in one rectangular battery according to the SAE J2464:2009 standard, and it was checked whether chain ignition occurred in other cells. The ignition of the battery was induced by penetrating the rectangular battery with a nail approximately 5 mm in diameter at a speed of 25 mm / sec (nail penetration method).
[0178] <Evaluation Criteria> Pass: If no fire occurs in any battery cell other than the one that has been penetrated by the nail. NG: If fire occurs in a battery cell other than the one pierced by the nail.
[0179] 3. Evaluation of weight change rate The composite material was cut into 10 cm x 10 cm sections, and its initial weight (W1) was measured at room temperature (approximately 25°C). The composite material was compressed using a UTM (Universal Testing Machine) Z030 (Zwick / Roell) with a compression test jig (circular jig: 9 cm in diameter).
[0180] The composite material was positioned between two compression test jigs and fixed between the jigs under a preload of 10kN. Then, the composite material was compressed from top to bottom at a rate of 1.3mm / min. Compression was stopped at the earlier of the following two points: when the thickness of the composite material reached 80% of its thickness before compression, or when a stress of 5kN was detected in the equipment due to the compression. The composite material was then removed and its weight (weight after compression W2) was measured.
[0181] During the aforementioned pressurization, the strain condition was set to 10%.
[0182] The weight change rate (%) was calculated according to formula 2 below.
[0183] [Formula 2] 100 × (W1-W2) / W1
[0184] In Equation 2, W1 is the initial weight of the composite material, and W2 is the weight of the composite material after pressurization, with the units of W1 and W2 being the same.
[0185] 4. Measurement of molecular weight The molecular weight of starch is evaluated using the following method.
[0186] (1) Manufacturing of the mobile phase Mobile phase A was prepared by filtering 1000 mL of a 150 mM NaNO3 aqueous solution containing 0.02 wt% NaN3 using a solvent clarification system (Millipore Millisolve Kit, MilliporeSigma).
[0187] (2) Preparation of sample solution A 25 mg sample was taken from the sample whose molecular weight was to be measured, mixed with 5 mL of a 150 mM NaNO3 aqueous solution containing 0.02 wt% NaN3, heated at 80°C for 20 hours, and then filtered through a 0.4 μm Nylon Syringe Filter to prepare the sample solution.
[0188] (3) GPC (Gel Permeation Chromatography) / MALS (Multi-Angle Light Scattering Detection) conditions The molecular weight is evaluated using the sample solution and mobile phase A in the following manner.
[0189] Measurement instrument: Agilent GPC (Agilent 1200 series, US) Stationary phase: Shodex OH-Pak 804 column and Shodex OH-Pak 80 column linked together Mobile phase: A; 0.02% NaN3, 150mM NaNO3 aqueous solution = 100 (v / v%) Flow rate: 0.4mL / min Stationary phase temperature: 25℃ Injection volume: 100μl (0.45μm filtered) Analysis time: 120 minutes
[0190] 5. Measurement of amylopectin and amylose content The amylopectin and amylose content of starch is evaluated according to the method described in the paper (Potato Research 31 (1988) 241-246). First, approximately 5 mg of the starch sample is dissolved in approximately 1 mL of sterile water to prepare the sample (Step 1), and then heated in a water bath at 95°C for approximately 15 minutes (Step 2).
[0191] Next, approximately 20 μl of the sample is placed in a cuvette (step 3), and approximately 980 μl of iodine solution is added and mixed (step 4).
[0192] Next, the absorbance of the sample mixed with the iodine solution at wavelengths of 525 nm and 700 nm is measured and recorded (Step 5). The absorbance is measured using the KLAB OPTIZEN POP model.
[0193] Approximately 20 μl of water was placed in another cuvette, and 980 μl of iodine solution was added and mixed (Step 6). The absorbance of the solution from Step 6 was measured and recorded at wavelengths of 525 nm and 700 nm, as in Step 5 (Step 7).
[0194] The absorbance obtained in step 7 was subtracted from the absorbance obtained in step 5, and the ratio (%) of amylose was confirmed according to formula 3 below (step 8).
[0195] [Formula 3] PA = 3.039 - U / L - 19.192
[0196] In Equation 3, PA is the percentage of amylose, U is determined by Equation 4 below, and L is determined by Equation 5 below.
[0197] [Formula 4] U = 7.154 × OD 700 / OD 525 [Formula 5] L = 3.048 × OD 700 / OD 525
[0198] In equations 4 and 5, OD 700 This is the value obtained by subtracting the absorbance at 700 nm measured in step 7 from the absorbance at 700 nm measured in step 5, and OD 525This value is obtained by subtracting the absorbance at 525 nm measured in step 7 from the absorbance at 525 nm measured in step 5.
[0199] 6. Evaluation of WVTR (Water Vapor Transmission Rate) The WVTR of the fire extinguishing system case is evaluated according to ASTM F1249 standards under conditions of 38°C and 100% relative humidity.
[0200] 7. Evaluation of solubility Solubility is evaluated based on the ASTM E1148-02 standard. The amount of sample that dissolves to the maximum extent in 100g of water at the measurement temperature (0°C or room temperature (approximately 25°C)) is evaluated according to the aforementioned standard, and the solubility is confirmed.
[0201] 8. Evaluation of Water Retention The moisture absorption of ceramic fiber wool was measured according to the ASTM-C 1511 standard. A 0.1 g test specimen (ceramic fiber wool) was floated on the surface of DI (Deionized) water maintained at approximately 21°C. Then, an Al metal mesh of approximately 0.25 inches was placed on top of the test specimen, and the test specimen was immersed to 5 inches below the surface of the DI (Deionized) water. This condition was maintained for approximately 15 minutes, after which the test specimen was removed, and one corner of the test specimen was secured with a clamp and held upright for approximately 1 minute. After that, the change in weight of the test specimen was measured to evaluate the moisture absorption.
[0202] Example 1. Manufacturing of composite materials A silica sol was produced by mixing distilled water, liquid sodium silicate, hydrochloric acid aqueous solution (hydrochloric acid concentration: approximately 33% by weight), monoammonium phosphate (NH4H2PO4), potassium acetate, and starch to create a mixture.
[0203] The starch used was corn starch with a weight-average molecular weight of approximately 51,000,000 g / mol and a weight ratio of amylose to amylopectin (amylose:amylopectin) of approximately 25:75.
[0204] As the liquid sodium silicate, we used No. 3 (KS) (No. 3 KS) from YOUNG IL CHEMICAL Co., Ltd. (Na2O content: approximately 9-10% by weight, SiO2 content: approximately 28-30% by weight, sodium silicate molar ratio (= 1.032 (SiO2 weight) / (Na2O weight)): approximately 3.1-3.3).
[0205] The solubility of monoammonium phosphate (N)(NH4H2PO4) in water at 25°C is approximately 29 g. The solubility of potassium acetate in 100 g of water at 0°C is approximately 216 g, and its solubility in 100 g of water at 25°C is approximately 268.6 g.
[0206] The mixing was carried out so that the weight ratio (W:S:A:N:K:T) of the distilled water (W), SiO2 (S) in the liquid sodium silicate, hydrochloric acid aqueous solution (A), monoammonium phosphate (N), potassium acetate (K), and starch (T) was approximately 100:5:4:10:50:5.
[0207] The pH of the mixture was approximately 5 to 6.
[0208] In the aforementioned mixture, the molar concentration of hydrochloric acid relative to distilled water was approximately 0.37, the molar concentration of monoammonium phosphate was approximately 0.85, and the molar concentration of potassium acetate was approximately 4.97.
[0209] In the aforementioned mixture, the following ΔT of formula 1 is obtained by the hydrochloric acid f The value is approximately 1.39, and the ΔT of the following formula 1 due to monoammonium phosphate is approximately 1.39. f The value is approximately 3.15, and the ΔT of the following formula 1 due to potassium acetate is approximately 3.15. f The value was approximately 18.47.
[0210] [Formula 1] △T f = K f × M × I
[0211] In Equation 1, K f is the freezing point depression constant of the distilled water, which is 1.86 K / m, M is the molar concentration of each ionic compound, and I is the number of moles of ions generated when 1 mole of the ionic compound completely dissociates.
[0212] The silica sol was prepared by stirring the mixture at a speed of approximately 500 rpm for approximately 15 minutes at room temperature (approximately 23°C).
[0213] A ceramic fiber wool (KCC, insulation board No. 1) (thickness: approximately 0.5-5 mm) was placed on a conveyor belt equipped with gel casting equipment, and the silica sol was impregnated into the ceramic fiber wool using spike rollers. Subsequently, while moving the conveyor belt, gelation was further promoted at room temperature (approximately 25°C) to form silica gel, thereby producing a composite material.
[0214] During the production of the composite material, the weight ratio (W:C) of the distilled water (W) in the silica sol to the ceramic fiber wool (C) was set to approximately 100:20.
[0215] The aforementioned ceramic fiber wool has a tensile strength of approximately 0.1 MPa, a compressive strength of approximately 150 kPa, a Young's modulus of approximately 3 MPa, and a density of approximately 2 g / cm³. 3The softening point is approximately 800°C. The tensile strength, compressive strength, and Young's modulus can be measured according to the KS K ISO 9073-3 standard. The ceramic fiber wool is cut to a width of approximately 50 mm and a length of approximately 200 mm, mounted on a UTM (Universal Testing Machine), and a stress-strain curve is obtained by stretching the ceramic fiber wool in the longitudinal direction at a speed of approximately 100 mm / min. Based on this curve, the tensile strength, compressive strength, and Young's modulus can be measured.
[0216] The water content in the composite material was approximately 51.6% by weight, the inorganic gel (silica gel) content was approximately 2.58% by weight, and the inorganic fiber (ceramic fiber wool) content was approximately 10.31% by weight.
[0217] Manufacturing of fire extinguishing systems The composite material was inserted into an aluminum can (case) used in the manufacture of prismatic batteries, and the opening was sealed to manufacture a fire extinguishing device. The aluminum can was made of an aluminum alloy, and the WVTR of the case was approximately 0 g / m². 2 It took about a day. As shown in Figure 4, the composite material (300) was inserted into the aluminum can (1001), and the lid (1002) was placed over it to manufacture the fire extinguishing device. For the rectangular battery case, a case with a width of about 9 cm, a height of about 12 cm, and a thickness of about 3 mm was used.
[0218] Example 2. A silica sol was prepared by mixing distilled water, liquid sodium silicate, an aqueous NaOH solution (NaOH concentration: approximately 35% by weight), an aqueous acetic acid solution (acetic acid concentration: approximately 33% by weight), monoammonium phosphate (NH4H2PO4), potassium acetate, and starch. The same substances as in Example 1 were used for the starch and liquid sodium silicate.
[0219] The mixing was carried out so that the weight ratio (W:S:B:A:N:K:T) of the distilled water (W), SiO2 (S) in the liquid sodium silicate, NaOH aqueous solution (B), acetic acid aqueous solution (A), monoammonium phosphate (N), potassium acetate (K), and starch (T) was approximately 100:10:0.1:1.6:10:40:1.
[0220] The pH of the aforementioned mixture was approximately 6 to 8.
[0221] In the aforementioned mixture, the molar concentration of NaOH relative to distilled water was approximately 0.01, the molar concentration of acetic acid was approximately 0.26, the molar concentration of monoammonium phosphate was approximately 0.87, and the molar concentration of potassium acetate was approximately 4.07.
[0222] In the mixture, the ΔT of formula 1 due to the NaOH f The value is approximately 0.03, and the ΔT of formula 1 due to acetic acid f The value is approximately 0.98, and the ΔT of formula 1 due to the monoammonium phosphate is approximately 0.98. f The value is approximately 3.23, and the ΔT of formula 1 due to potassium acetate is approximately 3.23. f The value was approximately 15.15.
[0223] The silica sol was prepared by stirring the mixture at a speed of approximately 500 rpm for approximately 15 minutes at room temperature (approximately 23°C).
[0224] The composite material and fire extinguishing device were manufactured in the same manner as in Example 1, except that the silica sol was used.
[0225] In the aforementioned composite material, the water content was approximately 54.7% by weight, the inorganic gel (silica gel) content was approximately 5.47% by weight, and the inorganic fiber (ceramic fiber wool) content was approximately 10.95% by weight.
[0226] Comparative Example 1. The composite material and fire extinguishing device were manufactured in the same manner as in Example 1, except that ceramic fiber wool exhibiting the moisture absorption properties shown in Table 1 below was used.
[0227] Comparative Example 2. A silica sol was prepared by mixing distilled water, liquid sodium silicate, aqueous hydrochloric acid solution (hydrochloric acid concentration: approximately 33% by weight), monoammonium phosphate (NH4H2PO4), potassium acetate, and starch. The same compounds as in Example 1 were used for the starch and liquid sodium silicate.
[0228] The mixing was carried out so that the weight ratio (W:S:A:N:K:T) of the distilled water (W), SiO2 (S) in the liquid sodium silicate, hydrochloric acid aqueous solution (A), monoammonium phosphate (N), potassium acetate (K), and starch (T) was approximately 100:1:4:10:40:1.
[0229] The pH of the mixture was approximately 5 to 6.
[0230] In the aforementioned mixture, the molar concentration of hydrochloric acid relative to distilled water was approximately 0.37, the molar concentration of monoammonium phosphate was approximately 0.85, and the molar concentration of potassium acetate was approximately 3.97.
[0231] In the mixture, the hydrochloric acid causes ΔT of formula 1 f The value is approximately 1.39, and the ΔT of formula 1 due to the monoammonium phosphate is approximately 1.39. f The value is approximately 3.15, and the ΔT of formula 1 due to potassium acetate is approximately 3.15. f The value was approximately 14.78.
[0232] The silica sol was prepared by stirring the mixture at a speed of approximately 500 rpm for approximately 15 minutes at room temperature (approximately 23°C).
[0233] The composite material and fire extinguishing device were manufactured in the same manner as in Example 1, except that the silica sol was used.
[0234] The water content in the composite material was approximately 56.7% by weight, the inorganic gel (silica gel) content was approximately 0.57% by weight, and the inorganic fiber (ceramic fiber wool) content was approximately 11.36% by weight.
[0235] Comparative Example 3. A mixture was prepared by mixing distilled water, liquid sodium silicate, an aqueous hydrochloric acid solution (hydrochloric acid concentration: approximately 33% by weight), and an aqueous NaOH solution (NaOH concentration: approximately 33% by weight), and a silica sol was produced. The same compound as in Example 1 was used as the liquid sodium silicate.
[0236] The mixing was carried out so that the weight ratio (W:S:A:B) of the distilled water (W), SiO2 (S) in the liquid sodium silicate, hydrochloric acid aqueous solution (A), and NaOH aqueous solution (B) was approximately 100:5:1.6:0.1.
[0237] The pH of the aforementioned mixture was approximately 6 to 8.
[0238] In the aforementioned mixture, the molar concentration of hydrochloric acid relative to distilled water was approximately 0.15, and the molar concentration of NaOH was approximately 0.01.
[0239] In the mixture, the hydrochloric acid causes ΔT of formula 1 f The value is approximately 0.57, and the ΔT of formula 1 due to NaOH f The value was approximately 0.03.
[0240] The silica sol was prepared by stirring the mixture at a speed of approximately 500 rpm for approximately 15 minutes at room temperature (approximately 23°C).
[0241] The composite material and fire extinguishing device were manufactured in the same manner as in Example 1, except that the silica sol was used.
[0242] The water content in the composite material was approximately 78.9% by weight, the inorganic gel (silica gel) content was approximately 3.95% by weight, and the inorganic fiber (ceramic fiber wool) content was approximately 15.79% by weight.
[0243] The evaluation results for the examples and comparative examples are shown in Table 1 below.
[0244] [Table 1]
[0245] The moisture absorption values in Table 1 represent the moisture absorption of ceramic fiber wool measured using the method described in "8. Water Retention Evaluation," and the weight change rates in Table 1 represent the weight change rates (weight change rates of composite material under 10% strain pressure conditions) measured according to the method described in "3. Weight Change Rate Evaluation."
[0246] The results in Table 1 show that including an inorganic gel (silica gel) and inorganic fibers (ceramic fiber wool) with appropriate moisture absorption capacity resulted in a low weight change rate, which led to appropriate results in the convection test and chain ignition test.
[0247] In Comparative Example 1, the inorganic fibers had low moisture absorption, resulting in a high weight change rate, which prevented us from obtaining appropriate results in the Convection Test and the Chain Ignition Test.
[0248] In Comparative Example 2, the hygroscopicity of the inorganic fibers was the same as in the example, but because the inorganic gel content was low, the weight change rate was high, and as a result, it was not possible to obtain appropriate results in the convection test and chain ignition test.
[0249] In Comparative Example 3, the hygroscopicity of the inorganic fibers was the same as in the example, and the inorganic gel content was also at a similar level to the example. However, the amount of ionic compound was not properly controlled during the formation process of the inorganic gel, resulting in a high weight change rate, which prevented obtaining appropriate results in the convection test and chain ignition test.
Claims
1. Vaporizing substances; and Contains inorganic gel, A composite material in which the weight change rate is 3% or less under a 10% pressure condition.
2. The composite material according to claim 1, wherein the vaporizing substance has a boiling point in the range of 80°C to 120°C.
3. The composite material according to claim 1, wherein the vaporizing substance is water.
4. The composite material according to claim 1, wherein the content of volatile substances is in the range of 40 to 90% by weight.
5. The composite material according to claim 1, comprising 1.5 parts by weight or more of inorganic gel per 100 parts by weight of a volatile substance.
6. The composite material according to claim 1, further comprising inorganic fibers.
7. The composite material according to claim 6, wherein the inorganic fibers have a moisture absorption of 55% or more according to the ASTM-C 1511 standard.
8. The composite material according to claim 6, comprising 5 to 100 parts by weight of inorganic fibers per 100 parts by weight of a volatile substance.
9. The composite material according to claim 6, wherein the inorganic gel is attached to the inorganic fibers, or the inorganic gel and inorganic fibers are intertwined with each other.
10. The composite material according to claim 1, further comprising an ionic compound.
11. The triangle T in equation 1 below f The composite material according to claim 10, wherein the value is in the range of 5 to 50: [Formula 1] △T f = K f × M × I In Equation 1, K f is the freezing point depression constant of the vaporized substance, M is the molar concentration of the ionic compound relative to the vaporized substance, and I is the number of moles of ions produced when 1 mole of the ionic compound dissociates.
12. The composite material according to claim 10, wherein the solubility of the ionic compound in 100 g of water at 25°C is 10 g or more.
13. The composite material according to claim 10, wherein the ionic compound is one or more selected from the group consisting of formate, acetate, carbonate, and sulfate.
14. The composite material according to claim 1, further comprising a carbonizable organic substance.
15. The composite material according to claim 14, further comprising a carbonization catalyst.
16. Cases; and A fire extinguishing device comprising a composite material according to any one of claims 1 to 15 present in the aforementioned case.